Phytochemical Analysis and Anti-Inflammatory Activity of The Combination of Trigona apicalis propolis Extract and Honey - Paula Mariana Kustiawan; Chaerul Fadly Mochtar Luthfi M; Sinta Ratna Dewi; Jati Pratiwi; Novia Misnawati Aisyiyah; Alfin Syahrian Dwi Nugraha; Irfan Muris Setiawan (Borneo Journal of Pharmacy, 2023)
Chronic inflammation is common in infectious diseases, rheumatoid arthritis, gout, and autoimmune diseases. However, using non-steroidal anti-inflammatory drugs (NSAIDs) is accompanied by dangerous side effects. Therefore, searching for safer alternative therapies without side effects is very important. A natural blend of ingredients produced by stingless bees from plants was potential as a remedy. Meanwhile, the potential of kelulut bee products from East Kalimantan as an anti-inflammatory is still unknown. This study aimed to compare the chemical composition of kelulut bee (Trigona apicalis) products and evaluate the anti-inflammatory effect of honey, propolis, and their combination. Propolis extract and honey were determined as secondary metabolites. An anti-inflammatory in vivo assay triggered the edema using carrageenan on male mice and measured its anti-inflammatory power value. Propolis extract and honey from T. apicalis have a promising anti-inflammatory effect and are significantly higher than the positive control. Meanwhile, combining propolis extract and honey did not enhance the anti-inflammatory effect. In addition, combining honey and propolis preparations with a ratio of 75 : 25 has a better effect on reducing edema volume than the other two combinations. Still, it is not better than the treatment with propolis extract or honey alone. The content of polyphenol compounds found in honey and propolis preparations is thought to have an important role in reducing edema volume.